2015
DOI: 10.5812/archcid.27495
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Euterpe edulis Martius, Mikania glomerata Spreng, and Mikania laevigata Schultz Bip. Extracts on Gastrointestinal Nematodes Toxocara canis and Ancylostoma caninum

Abstract: Background:Gastrointestinal parasitoses have high rates of morbidity and mortality. Each year about 3.5 billion people are affected by these diseases and 65,000 of them die, mostly in developing countries due to lack of basic sanitation, malnutrition, and poor access to medication. Thus, they constitute an important public health problem due to causing direct health problems related to lack of piped water, absence of sewage system, and lack of orientation. Objectives: Two in vitro assays were performed to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Artemisia absinthium prepared by Yildiz et al (2011), they were extracted its flower and oil using diethyl ether, while Ramos et al (2015) used hydro alcohols. Mikania glomerata and M. laevigata were dried and extracted with ethanol (Zamprogno et al 2015). Klimpel et al (2010) obtained extracts of the Allium cepa via ethanol, methanol, water, and chloroform, while Orengo et al (2016a) only used ethanol and water as solvents for plant extraction in their in vitro study, and only ethanol in their in vivo investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Artemisia absinthium prepared by Yildiz et al (2011), they were extracted its flower and oil using diethyl ether, while Ramos et al (2015) used hydro alcohols. Mikania glomerata and M. laevigata were dried and extracted with ethanol (Zamprogno et al 2015). Klimpel et al (2010) obtained extracts of the Allium cepa via ethanol, methanol, water, and chloroform, while Orengo et al (2016a) only used ethanol and water as solvents for plant extraction in their in vitro study, and only ethanol in their in vivo investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Anthelmintic effects of bioactive compounds in plants may vary depending on the stage of development of the worm. Two studies of Mikania glomerata using eggs and larvae revealed that the ethanol extract of Mikania glomerata at a concentration of 0.1–10 mg/mL could inhibit egg hatchability, while the ethanol extract of Mikania glomerata required at least 25 mg/mL and 50 mg/mL to reduce the number of larvae to 13.30% and 61.66%, respectively [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Terpenes are a group of plant chemical compounds putative of acting as anthelmintic in this study. Diterpenes of kaurane class compounds present in Mikania glomerata and Mikania laevigata showed anthelmintic activity in infective larvae of A. caninum in vitro [ 9 , 10 ]. Low-level anthelmintic betulin and lupeol present in Diospyros anisandra are of triterpene compound [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…has not been reported. The ethanolic extracts of Canthium manii (1,000 μg/ml), Mikania laevigata, M. glomerata , and Euterpe edulis (10,000 μg/ml) demonstrated a PEI of 90, 21.8, 25.9, and 21.1% ( 41 , 42 ). To obtain PEIs similar to those reported in the present study, Wabo et al ( 41 ) required at least 10 times more concentrated.…”
Section: Discussionmentioning
confidence: 99%